Identification of Candidate Blood mRNA Biomarkers in Intracerebral Hemorrhage Using Integrated Microarray and Weighted Gene Co-expression Network Analysis - Jin, Feng; Li, Lei; Hao, Yuehan; Tang, Ling; Wang, Yuye; He, Zhiyi (Frontiers in Genetics, 2021)
Purpose: Intracerebral hemorrhage (ICH) is a serious public health hazard due to its high morbidity, disability and mortality. Currently the exact molecular mechanisms of ICH are unknown. We tried to identify the ICH related candidate blood messenger RNA (mRNA) biomarkers by microarray analysis and weighted gene co-expression network analysis (WGCNA). Materials and Methods: We collected the blood samples from patients with ICH (n=4) and vascular risk factor (VRF) controls (n=4), and analyzed the mRNA expression profile by competitive endogenous RNA (ceRNA) microarray. Differentially expressed genes (DEGs) were conducted and then we construct a weighted gene co-expression network (WGCNA). Modules with clinical significance were distinguished. Then we downloaded two Gene Expression Omnibus (GEO) datasets (GSE24265 and GSE125512). Candidate mRNAs were identified by taking the intersection of DEGs in our microarray, interesting genes in the key module and DEGs in GSE24265. Functional analysis involving Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and construction of protein-protein interaction (PPI) network were conducted. Results: A total of 340 DEGs in our microarray were identified between ICH group and control group. Among the eight gene modules established by WGCNA, the yellow module containing 191 genes was the most strongly associated with ICH. Four candidate mRNAs (C3AR1, PAWR, ARNTL2 & LDLRAD4) were identified. In the early stage of ICH (within 24 hours), C3AR1, PAWR & ARNTL2 were highly expressed in the perihematomal tissue but low expressed in peripheral blood, and in the late stage (72 hours after the first blood draw), an obvious upward trend of C3AR1 and PAWR in peripheral blood were seen. Functional analysis showed that candidate mRNAs were concerned with multiple pathways such as Wnt signaling pathway and calcium signaling pathway. They might affect the process of ICH through neuroinflammation, cell apoptosis and pyroptosis. Conclusion: We identified four candidate blood mRNAs (C3AR1, PAWR, ARNTL2 & LDLRAD4) related to ICH. They showed different expression patterns in peripheral blood and perihematomal tissues and changed with time. They might play important roles in ICH through neuroinflammation, cell apoptosis and pyroptosis, and might shed the new light to novel biomarkers or therapeutic targets in ICH.